Avaliação microbiológica da efetividade dos campos de tecido não tecido (TNT) com diferentes gramaturas como barreira física para evitar contaminação microbiana - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Biosafety is a process that should be seen as a mechanism of protection, prevention, minimization or reduction of risks for both the patient and workers involved in health care. Cleaning, disinfection of fixed surgical surfaces and exposed parts of dental equipment and preparation of the surgical environment has been relevant, not relevant for infection control to ensure the safety of patients undergoing dental services. Among the surgical dressing or surgical field components, it stands out due to a wide contact area and direct interface between the accessories used and the surgical instruments that in turn maintain interaction with the surgical site. Thus, this research evaluates a microbiological barrier of Disposable Nonwoven Tissue Surgical Fields (TNT), sterilized by Ethylene Oxide and type SMS (Spunbonded / Meltblown / Spunbonded), sterilized by saturated wet steam; in different weights (20 g/m², 30 g/m², 40 g/m² and 60 g/m²) used in dental surgeries. The work consisted of 6 groups of samples composed of 10 samples of disposable surgical fields for each group in different weights. After previous sterilization of a Petry plate representing a contact surface, fields of SMS TNT type were detected on a plate and then contaminated with solution of microorganisms such as Escherichia coli, Enterococus faecalis and Staphylococcus aureus or the same procedure was performed. In the opposite direction, contaminate the surface of the Petry plate with microorganism solution and add TNT on a plate. The samples were collected from the groups after 15 minutes of sample contamination. Results: Regarding the occurrence of bacterial contamination, there was a statistically small difference between the quantities. Even with proper surface sterilization and dressing care, these fields were not fully utilized during maintenance of the aseptic chain. Conclusion: A sample of 60-gram SMS type TNT for both tissue contamination and contact surface contamination, better test results compared to the other TNTs in the different weights.
Keywords: Biossegurança; Campos cirúrgicos; Odontologia; Contaminação biológica; Biosafety; Surgical Fields; Dentistry and Biological Contamination; CNPQ::CIENCIAS DA SAUDE